Higher-Order Thinking in Foreign Language Learning - Bastos Ascensão; Ramos, Maria Altina Silva (Advances in Social Sciences Research Journal, 2017)
A project is being conducted in English as a foreign language (EFL), involving eleventh graders in formal and non-formal learning contexts, in a Portuguese high school. The goal of this study is to examine the impact of cognitive tools and higher-order thinking processes on the learning of EFL and achievement of larger processes oriented to action, involving problem solving, decision-making and creation of new products. YouTube videos emerge as cognitive tools in the process. Final results show major differences concerning learners’ achievements. Learners have developed higher-order processes oriented to action, in particular their ability to learn, to transfer the skills developed to different contexts and apply them effectively in EFL communicative situations. This paper discusses: a) major theories that support the integration of cognitive tools and thinking processes within the curriculum, focussing on the English language learning; b) some of the activities and materials; c) the final findings.